Étude de l’encapsulation des probiotiques et la fermentation du jus de grenade - Moulefida, Khadidja; Boukhatem, Imène (My University, 2024)
This thesis explores the physicochemical parameters influencing encapsulation, particularly the techniques of emulsification and extrusion, the encapsulation of probiotics by extrusion, their co-encapsulation, as well as their use in the fermentation of pomegranate juice. An agitation speed of 2, an alginate concentration of 2.5%, and a solidification time of 25 minutes allowed for the formation of capsules with appropriate characteristics for the encapsulation of the strains. In the in vivo test, a decrease in the feed conversion ratio of chickens from 0.8 to 1.1, as well as an increase in live weight of more than 200g compared to the control diet, were observed after administering the capsules (TF3, LGG, DC4) during the rearing weeks. After 35 days of storage, the LGG strain recorded the highest viability rate (92%), in contrast to the DC4 strain (64%). However, co-encapsulation revealed a significant decrease in strain viability, with reductions ranging from 1% to 64% compared to singly encapsulated strains. The number of inoculated bacteria increased after the fermentation of pomegranate juice from 2.92 × 10⁰ to 8.58 × 10⁰ for free bacteria, and from 1 × 10¹ to 1.64 × 10¹ for encapsulated bacteria, with a parallel decrease in reducing sugar content from 1.08 to 3.9 and a variation in pH from 0.1 to 0.2 units.
Keywords: probiotics; strains; bacteria; pomegranate juice; encapsulation; co-encapsulation; capsules; fermentation; viability